PENGARUH DIGITALISASI PERPAJAKAN DAN INSENTIF PERPAJAKAN TERHADAP PENGEMBANGAN UMKM TORAJA UTARA - Wilma Dian Ardiyanti; Srisetyawanie Bandaso; Septya Karla Palullungan; Serliana Tasik Tonapa (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the effect of tax digitalization and tax incentives on the development of North Toraja MSMEs. Digitalization aims to improve tax efficiency and compliance, while tax incentives are expected to encourage investment and growth in leading sectors. This study used 55 MSME samples in North Toraja Regency. The data analysis techniques used were descriptive analysis and verification analysis, namely: Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, and Hypothesis Testing with Partial Test (t test) and Simultaneous Test (F test). Keywords : tax digitalization; tax incentives; MSME Development